The Syriac Orthodox Church of Antioch: History in the making: The Syriac Orthodox Church of Antioch is marking its 1,500 Jubilee Year of Mor Jacob de Serugh (521+) (St Jacob of Serugh). - Issa, Theodora (2021)
In response to the call by His Holiness Moran Mor Ignatius Aphrem II, Patriarch of Antioch and all the East, the Supreme Head of the Universal Syriac Orthodox Church, and despite the restrictions imposed by COVID-19 and its variants, the Syriac Orthodox Community worldwide answered the call, and have been learning more about this great saint and poet through holding online sessions, translating his poems into different languages, airing television programs, publishing books, brochures and booklets, and producing YouTube videos on the life of this saint.